Racing Against the Vocabulary Gap: Matthew Effects in Early Vocabulary Instruction and Intervention. (January 2019) - Coyne, Michael D.; McCoach, D. Betsy; Ware, Sharon; Austin, Christy R.; Loftus-Rattan, Susan M.; Baker, Doris L.
We investigated whether individual differences in overall receptive vocabulary knowledge measured at the beginning of the year moderated the effects of a kindergarten vocabulary intervention that supplemented classroom vocabulary instruction. We also examined whether moderation would offset the benefits of providing Tier-2 vocabulary intervention within a multitiered-system-of-support (MTSS) or response-to-intervention framework. Participants included students from two previous studies identified as at risk for language and learning difficulties who were randomly assigned in clusters to receive small-group vocabulary intervention in addition to classroom vocabulary instruction ( n = 825) or to receive classroom vocabulary instruction only ( n = 781). A group of not-at-risk students ( n = 741) who received classroom vocabulary instruction served as a reference group. Initial vocabulary knowledge measured at pretest moderated the impact of intervention on experimenter-developed measures of expressive vocabulary learning and listening comprehension favoring students with higher initial vocabulary knowledge. Tier-2 intervention substantially counteracted the Matthew effect for target word learning. Intervention effects on listening comprehension depended on students' initial vocabulary knowledge. Implications present benefits and challenges of supporting vocabulary learning within an MTSS framework.